Differential Intensive Therapy for Generalized Peritonitis and Abdominal Sepsis - Ye. V. Grigoryev; Yu. A. Churlyaev (Общая реаниматология)
The study was undertaken to substantiate a differential choice of intensive care of abdominal sepsis on the basis of its clinical and pathogenetic types. Clinical and biochemical parameters were retro- and prospectively studied in 60 patients diagnosed as having generalized peritonitis and abdominal sepsis. The patients were divided into 3 groups in accordance with their clinical and pathogenetic characteristics. The clinical and pathogenetic types of the course of abdominal sepsis were identified. The first type required additions of the above complex of intensive care by supplementing enteral detoxification. In the second clinical and pathogenetic type of abdominal sepsis, therapy is extended through simultaneous intravenous administration of perfluorane and enteral detoxification with an enterosorbent. In the third type, therapy is extended through intravenous infusion of perfluorane, followed by enteral detoxification.